Two cross coupled and Madgwicks filter for estimation of multi-channel dividing systems - Nader Abdullah Kadhim; Ali jawad Alrubaie; Ameer Al-khaykan (Indonesian Journal of Electrical Engineering and Computer Science, 2022)
The estimates of Rayleigh fading channels are rapidly changing in multi carrier direct sequence code division multiple access (MC-DS-CDMA) multiplexing systems. The most widely accepted answer to this issue is the conventional solution least square (LS) or mean square error estimator (MMSE) using the recursive least squares algorithm (RLS) or the least mean squares (LMS) algorithm. In much of the previous work, only one Kalman filter was used for estimation. In this paper, a Kalman filter is used with a Madgwicks filter together to satisfy the fading problems. However, this requires a priori evaluation of auto regressive (AR) parameters. A standard solution involves the first matching of the auto-completion function of the applying the AR method to Jakes' problem and then tackling it (YWE). Even more the results procedure is limited to crowd constraints and is related to an AR+ process of noise, an approximation considered. In fact, depending on simulation findings, high-AR models outperform conventional models on the basis of spectral estimate and bit error margins (BER). Nevertheless, in order to save costs of computing, the 5-D model of AR is a possibility. The proposed process outperforms edge of art competitors in terms of bit error rate as demonstrated by results.